1996
DOI: 10.1111/j.1432-1033.1996.0842u.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping and Immunoneutralization of Recombinant Human Stem‐Cell Factor

Abstract: The epitope regions of three anti-[stem-cell factor (SCF)] Ig have been mapped by characterization of immunoreactivities against truncated forms of SCF in imrnunoblots and against synthetic peptides in solution-phase competition ELISA. Two of the antibodies, mAb 7H6 and mAb 8H7A, were raised against Escherichia coli-derived human SCF-(1-164) while the third, polyclonal antibody (pAb) 1337, was raised against a peptide corresponding to residues 3-31 of human SCF. The epitopes of mAbs 7H6 and 8H7A have been mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The SCF/KIT structure can now be used to rationalize previous biochemical and functional data mapping SCF/KIT interaction. Mutagenesis and antibody mapping data on SCF implicate the first few N‐terminal residues before Cys4 (Langley et al , 1994), the regions flanked by residues 61–65 and 91–95 (Mendiaz et al , 1996) or the region of residues 79–97 (Matous et al , 1996), being important for KIT binding. These regions, to some extent, differ from the SCF/KIT interfaces in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The SCF/KIT structure can now be used to rationalize previous biochemical and functional data mapping SCF/KIT interaction. Mutagenesis and antibody mapping data on SCF implicate the first few N‐terminal residues before Cys4 (Langley et al , 1994), the regions flanked by residues 61–65 and 91–95 (Mendiaz et al , 1996) or the region of residues 79–97 (Matous et al , 1996), being important for KIT binding. These regions, to some extent, differ from the SCF/KIT interfaces in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Arg121 and Asp124 are adjacent to the main N‐linked glycosylation site, which is not involved in binding (see below), and Asp128 is absent in the 1‐127 truncation mutant that retains full receptor‐binding activity (Langley et al ., 1994). Moreover, a study of human‐murine SCF chimeras narrowed the important receptor recognition epitopes to within residues 1‐35 and 79‐97 (Matous et al ., 1996), and the epitope of a neutralizing monoclonal antibody was mapped to the region of residues 60‐95 (Mendiaz et al ., 1996) and 79‐97 (Matous et al ., 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by using antibodies that neutralize different epitopes on SCF, it was demonstrated that the regions flanked by amino acids 61-65 and 91-95 are also essential for SCF activity (31). In general, the regions mapped by biochemical methods are located in close proximity at the tail region of each SCF protomer.…”
Section: Domain Swapping and The Covalent Dimer Of Scfmentioning
confidence: 99%